Design of a trigeneration system using high temperature fuel cells - Carvalhinho, Ana Paula (2009)
In this paper a CHCP system, using a high temperature fuel cell (SOFC) and an absorption chiller, is designed in order to meet the energetic needs of a hospital for electricity, cooling, heating and hot water. The hospital load profile was determined taking into consideration the hourly energy consumption for four different typical days in the year. The CHCP system was designed so that the fuel cell meets the electrical needs of the hospital and, since the SOFC does not produce enough thermal energy, a boiler has to be considered. The CHCP system designed is not financially feasible.